Smart Energy‐Absorbing Aerogel‐Based Honeycombs with Selectively Nanoconfined Shear‐Stiffening Gel. Issue 4 (2nd February 2023) - Cheng, Qingqing; Lyu, Jing; Shi, Nan; Zhang, Xuetong
Abstract: Aerogels, shaped as fibers, films, as well as monoliths, have demonstrated a plethora of applications in both academia and industry due to charming properties including ultralow density, large specific surface area, high porosity, etc., however studies on more complicated aerogel forms (e.g., honeycombs) with more powerful applications have not been fully explored. Herein, the Kevlar aerogel honeycomb is firstly constructed through a dry ice‐assisted 3D printing method, where the Kevlar nanofiber ink is printed directly in dry ice freezing atmosphere, followed by supercritical fluid drying. The subsequent 3D Kevlar/shear‐stiffening gel (SSG) honeycomb (3D‐KSH) can be obtained by selective nanoconfining of SSG into nanopores of the aerogel skeleton wall (with the loading amount of 93 wt%) rather than into open honeycomb channels, solving the leakage, creep deformation, and shape design infeasibility of the SSG. Combining the advantages of Kevlar, honeycomb and SSG, the fabricated 3D‐KSH shows obvious smart responsive behavior to external stimulus. Additionally, the 3D‐KSH has high strain rate sensitivity (sensitivity factor of 4.16 × 10 −4 ) and excellent impact protection performance (energy absorption value up to 176 J g −1 at the strain rate of 6300 s −1 ), which will significantly broaden application prospect in some intelligent protection fields. Abstract : 3D Kevlar/shear‐stiffening gel honeycomb is firstly constructed by selective nanoconfining of shear‐stiffening gel into the aerogel skeleton wall of the 3D printed Kevlar aerogel honeycomb, which shows obvious smart responsive behavior, high strain rate sensitivity, and excellent impact protection performance, significantly broadening its application prospect in some intelligent protection fields.